Evaluating the Evidence for a Link Between Glycemic Control and Keratosis Pilaris in Type 2 Diabetes: A Systematic Review - Gede Agus Indra Pramana; Rona Nisrina Ananda (The International Journal of Medical Science and Health Research, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a systemic metabolic disorder frequently associated with a wide spectrum of cutaneous manifestations, which often reflect the underlying degree of glycemic control. Keratosis pilaris (KP), a common benign disorder of follicular keratinization, has been anecdotally linked to metabolic disturbances such as obesity and insulin resistance. However, a direct, evidence-based correlation between glycemic control, measured by glycated hemoglobin (HbA1c), and the severity of KP in the T2DM population has not been systematically evaluated, representing a significant gap in the literature. Methods: A systematic review was conducted following PRISMA guidelines. PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases were searched for observational studies published up to October 2024. The primary search sought studies directly correlating HbA1c levels with KP severity in adult T2DM patients. Due to the absence of such studies, the search was broadened to include studies assessing KP in populations with related metabolic conditions (obesity, metabolic syndrome, insulin resistance). The Risk of Bias in Non-randomized Studies of Interventions (ROBINS-I) tool was used for quality assessment. Results: The systematic search yielded no studies that directly investigated the correlation between HbA1c levels and KP severity in patients with T2DM. The review of broadened search results included 16 observational studies. These studies demonstrated a high prevalence of KP in populations with metabolic dysregulation, with rates of 42% to 64.7% reported in obese cohorts. Crucially, one study identified a statistically significant association between KP and the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) score in obese adolescents (). Other studies, however, did not find a significant link between KP and insulin levels, highlighting inconsistencies in the existing indirect evidence. Discussion: The principal finding of this review is the definitive lack of direct evidence on the topic, which constitutes a critical research gap. Despite this, a strong biological rationale for a positive correlation is proposed, synthesized from indirect clinical and basic science evidence. Pathophysiological pathways involving hyperglycemia-induced Advanced Glycation End Products (AGEs) are known to impair keratinocyte differentiation and skin barrier function. Concurrently, compensatory hyperinsulinemia in T2DM can activate Insulin-like Growth Factor-1 (IGF-1) receptors on follicular keratinocytes, promoting hyperproliferation—a key pathological feature of KP. This dual mechanism suggests that poor glycemic control could both initiate and exacerbate the follicular hyperkeratosis characteristic of KP. Conclusion: While direct clinical evidence is currently absent, a compelling, mechanistically plausible link exists between poor glycemic control in T2DM and the severity of Keratosis Pilaris. This review highlights the urgent need for well-designed observational studies to investigate this association. If confirmed, KP could serve as a readily observable cutaneous marker for underlying insulin resistance or deteriorating glycemic control, prompting earlier clinical intervention.